30-Day Journey with Jane Austen - Duquette, Natasha (30-Day Journey., 2020)
Beloved across the centuries, Jane Austen is widely celebrated for her novels depicting life and romance in eighteenth-century England and the engrossing characters that fill their pages. Whether you read Pride and Prejudice every year or are encountering Austen's wit and wisdom for the first time, this journey provides the perfect way to engage the thought of one of the most popular novelists ever to pick up a pen.